Kinerja Portofolio Optimal Pada Saham Syariah - Mutmainah Mutmainah; Imron Mawardi (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
This study wants to describe whether an optimal portfolio which was formed in 2013-2015 it was good in 2016 compared to the performance of Jakarta Islamic Index and described as it is. The formation of the portfolio using single index model and the performance is measured by using the Sharpe index. This research is quantitative descriptive research. This research uses secondary data, carried out on the stock consistently at the Jakarta Islamic Index in January 2013-July 2016. Based on data, there were 18 shares actively and four stocks forming optimal portfolio composed of AKRA, TLKM, ICBP, and UNVR. Optimal portfolio performance in 2016 was 0,720 while the performance of the market was 0,676. With the results showed that it formed a good portfolio because the result was higher than the market. So investors or investment managers can make this portfolio as investment considerations.